2021
DOI: 10.3892/etm.2021.9822
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal mucosal microbiota composition of patients with acquired immune deficiency syndrome in Guangzhou, China

Abstract: Acquired immune deficiency syndrome, caused by the human immunodeficiency virus (HIV), has been associated with intestinal dysbiosis, which includes an increase in the number of mucosa-associated pathobionts. In the present study, the intestinal mucosal microbiota patterns of HIV-infected patients were compared with those of healthy individuals in a population from Guangzhou, China. The gut microbiota of intestinal mucosal samples from 12 patients with HIV (transmission routes included sex and intravenous drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…(Kim et al, 2013) Shewanellae is also being increasingly linked to bacteremia, soft tissue infections, and otitis media. (Janda and Abbott, 2014) A recent study found that Halomonas and Shewanella were significantly higher in the peritumoral regions of GC patients than in healthy people, indicating a potential role for these two genera in the occurrence of GC (Ling et al, 2019) The abundance of Halomonas is also significantly higher in the gut flora of patients with bronchial asthma (Tikunov et al, 2021) and is linked to HIV-associated microbiome alterations (Xu et al, 2021).…”
Section: Bile Reflux Alters the Composition Of The Gastric Mucosa Mic...mentioning
confidence: 99%
“…(Kim et al, 2013) Shewanellae is also being increasingly linked to bacteremia, soft tissue infections, and otitis media. (Janda and Abbott, 2014) A recent study found that Halomonas and Shewanella were significantly higher in the peritumoral regions of GC patients than in healthy people, indicating a potential role for these two genera in the occurrence of GC (Ling et al, 2019) The abundance of Halomonas is also significantly higher in the gut flora of patients with bronchial asthma (Tikunov et al, 2021) and is linked to HIV-associated microbiome alterations (Xu et al, 2021).…”
Section: Bile Reflux Alters the Composition Of The Gastric Mucosa Mic...mentioning
confidence: 99%
“…Halomonas and substance use disorder. Previously, Halomonas was found to be significantly elevated in the intestines of HIV-infected patients and was associated with sexual transmission of HIV (Xu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%